Ayurveda Perspective Of Drug- Drug Interactions – A Review - Vivek; Suneha (International Research Journal of Ayurveda & Yoga, 2021)
Drug safety is a fundamental concept in medical practice. Ayurveda is a holistic approach of medicine which has elaborated the causes and methods of drug-induced consequences along with preventive measures in classical texts. The aim of Ayurveda is to prevent normal health and curing the diseased one. Present literature review was conducted from the various compilation of Ayurveda and electronic database with search terms of ‘Vyapad’, ‘Viruddha’, ‘Ahita’, ‘herb–herb interaction’, ‘Asatmya’, ‘Prakritiviruddha’ etc. Ayurveda texts have mentioned various causes for Adverse Drug Reaction which seems to be not much different than those explained in modern such as, excessive effects, drug interaction, drug intolerance in susceptible patients, and drug allergy. The word ADR may not be found in Ayurvedic literature but the concepts and safety issues are vibrant throughout the texts of Ayurveda. The various concepts of drug interactions in Ayurveda sound similar to that of modern pharmacovigilance.